Regional and temporal differences in the associations between cardiovascular disease and its classic risk factors: an analysis of 49 cohorts from 11 European countries - Reinikainen, Jaakko; Kuulasmaa, Kari; Oskarsson, Viktor; Amouyel, Philippe; Biasch, Katia; Brenner, Hermann; De Ponti, Roberto; Donfrancesco, Chiara; Drygas, Wojciech; Ferrieres, Jean; Grassi, Guido; Grimsgaard, Sameline; et al. (European journal of preventive cardiology, 2024)
The regional and temporal differences in the associations between cardiovascular disease (CVD) and its classic risk factors are unknown. The current study examined these associations in different European regions over a 30-year period.The study sample comprised 553 818 individuals from 49 cohorts in 11 European countries (baseline: 1982-2012) who were followed up for a maximum of 10 years. Risk factors [sex, smoking, diabetes, non-HDL cholesterol, systolic blood pressure (BP), and body mass index (BMI)] and CVD events (coronary heart disease or stroke) were harmonized across cohorts. Risk factor-outcome associations were analysed using multivariable-adjusted Cox regression models, and differences in associations were assessed using meta-regression. The differences in the risk factor-CVD associations between central Europe, northern Europe, southern Europe, and the UK were generally small. Men had a slightly higher hazard ratio (HR) in southern Europe (P = 0.043 for overall difference), and those with diabetes had a slightly lower HR in central Europe (P = 0.022 for overall difference) compared with the other regions. Of the six CVD risk factors, minor HR decreases per decade were observed for non-HDL cholesterol [7% per mmol/L; 95% confidence interval (CI), 3-10%] and systolic BP (4% per 20 mmHg; 95% CI, 1-8%), while a minor HR increase per decade was observed for BMI (7% per 10 kg/m2; 95% CI, 1-13%).The results demonstrate that all classic CVD risk factors are still relevant in Europe, irrespective of regional area. Preventive strategies should focus on risk factors with the greatest population attributable risk.All classic cardiovascular disease (CVD) risk factors are still relevant in Europe, irrespective of regional area.The differences in the associations of CVD risk factors with overt CVD between regions of Europe are generally small.Minor temporal hazard decreases were observed for non-HDL cholesterol and systolic blood pressure, while a minor hazard increase was observed for body mass index.
Veröffentlicht: 17 November 2023
Gesehen am 15.04.2024